2014
DOI: 10.1089/bfm.2014.0028
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Introduction of Prelacteal Feeds in the Maldives

Abstract: Health professionals need to distinguish between religious and cultural practices in order to develop appropriate health education programs to reduce the unnecessary use of early additional feeds. Understanding the barriers related to the initiation of breastfeeding after cesarean section is also important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 26 publications
4
29
0
1
Order By: Relevance
“…Partial breastfeeding rates and predominant breastfeeding rates at 1 and 3 months are high in the Maldives compared with other Asian countries . Exclusive breastfeeding rate is very low due to early introduction of complementary foods.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Partial breastfeeding rates and predominant breastfeeding rates at 1 and 3 months are high in the Maldives compared with other Asian countries . Exclusive breastfeeding rate is very low due to early introduction of complementary foods.…”
Section: Discussionmentioning
confidence: 93%
“…Formula milk was introduced early by some mothers, having the perception that breastmilk alone is not sufficient for the infant. The early introduction of foods such as honey, carries a risk of Clostridium infection and giving other foods may change the nature of the human microbiome which is a crucial factor in determining obesity and chronic disease later in life …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Marketing of BMS within the health care system undermines mothers' confidence in breastfeeding (Parry, Ip, Chau, Wu, & Tarrant, 2013) and has been observed across South and Southeast Asia even when national legislation is in place to limit it (Barennes, Slesak, Goyet, Aaron, & Srour, 2016;Durako, Diallo, Thompson, & Aronson, 2016a;Durako, Diallo, Thompson, & Aronson, 2016b;Hidayana et al, 2016;Sobel et al, 2011). Prior research has shown that early use of BMS for feeding of newborns can increase the likelihood of continued BMS use for infant feeding and contribute to early breastfeeding cessation (Onah et al, 2014;Patil et al, 2015;Raheem, Binns, Chih, & Sauer, 2014).…”
mentioning
confidence: 99%
“…[10][11][12][13][14] Anne sütü ile beslemenin sürdürülmesini etkileyen demogra k, biyolojik, psikolojik ve sosyal pek çok belirleyici faktör olmakla birlikte, yapılan çalışmalar annenin emzirmeye ilişkin tutumunun bebeğini besleme davranışı üzerinde önemli etkisi olduğunu bildirmektedir. [15][16][17] Özellikle olumsuz emzirme tutumuna sahip annelerde formül mama ya da ek besinlere başlama oranının arttığına dikkat çekilmektedir. [18][19][20] Ancak ülkemizde bebeğin beslenmesine ilişkin annenin tutumunu değerlendiren yeterli çalışma olmamasının yanı sıra uygun bir ölçüm aracı da bulunmamaktadır.…”
unclassified